Gona, Ethiopia: microcosm of the stone age - Rogers, Michael J.; Semaw, Sileshi; Stinchcomb, Gary E.; Quade, Jay; Levin, Naomi E.; Cauche, Dominique (Handbook of Pleistocene Archaeology of Afric, 2023)
The Gona paleoanthropological field project in the Afar region of Ethiopia has long been associated with the earliest Oldowan stone tools. However, over the last 20 years, ongoing research at Gona has expanded its contributions considerably, producing fossils of Ardipithecus kadabba, Ardipithecus ramidus, and Homo erectus, as well as additional archaeological evidence of the earliest Oldowan and early Acheulean. Moreover, in the last few years, the Gona team has turned its attention to the younger deposits exposed in its study area and discovered a surprising number of Middle Stone Age (MSA) and Later Stone Age (LSA) archaeological sites, mostly from the Late Pleistocene to the early-middle Holocene. While any sedimentary sequence is incomplete by virtue of episodic depositional and erosional events over time, we are struck by the relative completeness of the archaeological sequence at Gona (Quade et al., 2008). The hominin fossils attract deserved attention, but the Gona project may ultimately be best known for preserving arguably the most extensive, detailed, and continuous Stone Age or Paleolithic archaeological sequence in the world, all contained within a small 25 km × 10 km area, approximately half of the total project area.
Keywords: dept.ant

Buzo or recycler: waste collecting as gift exchange in the context of a new waste regime - Skoczen, Kathleen N.; Caram Ibarra, Maria A (Practicing Anthropology, 2023)
The Dominican Republic (DR) experienced an economic boom related to tourism development over the last 30 years. Subsequently, consumption has increased, accompanied by an exponential growth in inorganic waste. Without adequate solid waste management, an environmental crisis has developed. Plastic waste litters roadsides, streets, streams, and beaches, threatening the very industry that enabled it. Informal waste collectors are on the front line of addressing, if not alleviating, the crisis but are regarded as marginal and inconsequential. A new waste regime is inevitable and imminent. Waste collectors are justifiably concerned that new systems may threaten their livelihoods. As such, they leverage their work, vis-à-vis a gift economy, to place themselves as essential to addressing the environmental crisis.
Keywords: dept.ant

The wastescapes of Samaná - Skoczen, Kathleen; Pantaleón, Natividad; Abreu, Daniel (Practicing Anthropology, 2023)
We conducted a formative research study on the peninsula of Samaná, in the northeast corner of the Dominican Republic, focused on how people viewed, categorized, and handled solid waste. With the passage of a new law, a motivated government administration is now addressing the solid waste crisis on the peninsula. Here, we examine some of the pre-existing attitudes about the solid waste of Samaná residents. Results from the study reveal that, contrary to many assumptions, local Dominicans are aware of the waste crisis and, in fact, are often depressed and anxious over it, even as they feel angry and helpless about how to resolve it. On closer examination and drawing on Appadurai’s theoretical framework of “-scapes,” we can understand that the waste crisis is not a local problem, and, as such, sustainable solutions need to include a broader effort to control plastic entering the environment.
Keywords: dept.ant

Language and racial capitalism: linguistic anthropological approaches to minoritized labor, standard language, and racial bias - McGill, Kenneth (Transforming Anthropology, 2023)
This article examines racial capitalism from a semiotic perspective, arguing that economic value, like language and race, can be described in situated and indexical terms. I attempt to show how raciolinguistic bias in and around the workplace is linked to a larger labor market in which minoritized labor is reproduced in a systemic way, and to explore hegemonic formations of racialization in the workplace and beyond. The jumping-off point for much of my argument is the work of the historian and political theorist Cedric Robinson.
Keywords: dept.ant; labor; language; markets; minoritization; peer-reviewed; race

Fluvial response to Quaternary hydroclimate in eastern Africa: Evidence from Gona, Afar, Ethiopia - Stinchcomb, Gary E.; Quade, Jay; Levin, Naomi E.; Iverson, Nels; Dunbar, Nelia; McIntosh, William; Arnold, Lee J.; Demuro, Martina; Duval, Mathieu; Grün, Rainer; Zhao, Jian-xin; White, Marie; et al. (Quaternary Science Reviews, 2023)
The Busidima Formation in the Afar region, Ethiopia, spans the Quaternary and records the cultural evolution of the genus Homo. Yet, the Middle Pleistocene to Holocene fluvial environments in which early humans lived are undersampled in eastern Africa. This paper examines the stratigraphy, geochronology and paleoenvironments of the newly designated Odele Member of the uppermost Busidima Formation (<152 thousand years ago (ka)), which has received little attention despite representing a critical period in the evolution of early Homo sapiens and its migration out of Africa. The Odele Member is 40–50 m thick and is dated using tephrochronology, radiometric, luminescence, and electron spin resonance techniques. The member spans 151 to 7 ka, defined at the base by the widespread Waidedo Vitric Tuff (WAVT, 151 ± 16 ka modeled age and 95.4% credible interval - C.I.). There are two prominent erosional unconformities in the Odele Member, a lower one after the WAVT deposition with a modeled 95.4% C.I. range of 124–97 ka; and an upper one involving widespread alluvial fan incision commencing between 21.7 and 12.9 ka. The uppermost Odele Member also contains black, organic-rich mats, redox features, reed casts, and freshwater gastropods marking wetter conditions during the terminal Pleistocene and Early Holocene. A black, fine-grained relict soil coeval with the Halalalee paleosol bounds the top of the Odele Member and has mollic and vertic properties, weathering since ∼12 ka. These incision events and prominent paleosol development near/at the top of the Busidima Formation document Middle to Late Pleistocene Awash River incision to its present-day course. Paleo-rainfall estimates suggest that the Early Holocene-age Halalalee paleosol weathered under a climate with mean annual rainfall 10–15% higher than today. A compilation of radiocarbon ages from aquatic gastropods, carbonized wood and charcoal from the upper Odele Member shows wetter and possibly more vegetated conditions during late marine isotope stage (MIS) 3 and the African Humid Period (AHP) that are tightly coupled with precession-driven summer insolation maxima. These key findings suggest that periods of incision, aggregation, and landscape stability in the Odele Member have an orbital precession pacing. The Odele Member revises upward the age of the Busidima Formation to 7 ka, showing that it spans into the Holocene and now includes Middle and Later Stone Age archaeological traditions.
Keywords: Electron spin resonance; Ethiopian rift; Fluvial aggradation; Fluvial incision; Paleosol; Radiocarbon; Tephrochronology; U-series; dept.ant; pIR-IRSL; peer-reviewed

The endocast from Dana Aoule North (DAN5/P1): A 1.5 million year-old human braincase from Gona, Afar, Ethiopia - Bruner, Emiliano; Holloway, Ralph; Baab, Karen L.; Rogers, Michael J.; Semaw, Sileshi (American Journal of Biological Anthropology, 2023)
The nearly complete cranium DAN5/P1 was found at Gona (Afar, Ethiopia), dated to 1.5–1.6 Ma, and assigned to the species Homo erectus. Its size is, nonetheless, particularly small for the known range of variation of this taxon, and the cranial capacity has been estimated as 598 cc. In this study, we analyzed a reconstruction of its endocranial cast, to investigate its paleoneurological features. The main anatomical traits of the endocast were described, and its morphology was compared with other fossil and modern human samples. The endocast shows most of the traits associated with less encephalized human taxa, like narrow frontal lobes and a simple meningeal vascular network with posterior parietal branches. The parietal region is relatively tall and rounded, although not especially large. Based on our set of measures, the general endocranial proportions are within the range of fossils included in the species Homo habilis or in the genus Australopithecus. Similarities with the genus Homo include a more posterior position of the frontal lobe relative to the cranial bones, and the general endocranial length and width when size is taken into account. This new specimen extends the known brain size variability of Homo ergaster/erectus, while suggesting that differences in gross brain proportions among early human species, or even between early humans and australopiths, were absent or subtle.
Keywords: Homo erectus; Homo ergaster; Lower Pleistocene; brain evolution; dept.ant; human evolution; paleoneurology; peer-reviewed